Catecholamine-producing cells in the synovial tissue during arthritis: modulation of sympathetic neurotransmitters as new therapeutic target. Issue 10 (24th May 2010) - Capellino, Silvia; Cosentino, Marco; Wolff, Christine; Schmidt, Martin; Grifka, Joachim; Straub, Rainer H
Abstract : Background: The proinflammatory and anti-inflammatory role of the sympathetic nervous system in early and late inflammation is an unresolved paradox. A drastic loss of sympathetic nerve fibres in the synovial tissue of patients with rheumatoid arthritis (RA) has previously been demonstrated. The presence of tyrosine hydroxylase (TH)-positive cells in RA and osteoarthritis (OA) has been determined, but the role of these cells in inflammation is still unclear. Objective: To characterise TH-positive cells in inflamed RA and OA synovial tissue and to study their role in inflammation. Methods: Synovial samples were obtained from 32 patients with OA and 19 patients with RA and from 10 control patients. Synovial tissue samples were used for immunofluorescence staining. Synovial cells were isolated by tissue digestion and immediately used for cell culture. For in vivo experiments, collagen type-II arthritis in DBA/1J mice was induced. Results: TH+ cells were present only in inflamed tissue and not in controls. Catecholamine-storing vesicles and vesicular monoamine transporter 2 (VMAT2) were identified in the synovial tissue. Experimental increase of cytoplasmic catecholamines by VMAT2 blockade strongly reduced tumour necrosis factor (TNF) independently of canonical extracellular β-adrenergic signalling. In addition, VMAT2 blockade increased cyclic AMP (cAMP) and cAMP responsive element binding protein, responsible for TNF inhibition. In vivo, appearance of VMAT2 positive cells was confirmed. VMAT2 blockade ameliorated inflammation also in vivo. Conclusions: This study demonstrates that local catecholamine-producing cells start to replace sympathetic nerve fibres around the onset of disease, and modulation of locally produced catecholamines has strong anti-inflammatory effects in vivo and in vitro.